Physiological and Pathophysiological Consequences of a 25-Day Ultra-Endurance Exercise Challenge - Tiller, Nicholas B.; Chiesa, Scott T.; Roberts, Justin D.; Turner, Louise A.; Jones, Siana; Romer, Lee M. (Frontiers in Physiology, 2019)
Background. This case-report characterised the respiratory, cardiovascular, and nutritional/gastrointestinal (GI) responses of a trained individual to a unique ultra-endurance exercise challenge. Case Presentation. A male athlete (age 45 y; V̇O2max 54.0 mL∙kg−1∙min−1) summited 100 mountains on foot in 25 consecutive days (all elevations >600 m). Measures. Laboratory measures of pulmonary function (spirometry, whole-body plethysmography, single-breath rebreathe), respiratory muscle strength (maximum static mouth-pressures), and cardiovascular structure and function (echocardiography, electrocardiography, large vessel ultrasound, flow-mediated dilatation) were made at baseline and 48 h post-challenge. Dietary intake (four-day food diary), self-reported GI symptoms and plasma endotoxin concentrations were assessed at baseline, pre/post mid-point, pre/post end-point and 48 h post-challenge. Results. The challenge was completed in a total exercise time of 142 h (5.3 ± 2.8 h∙d−1), with a distance of 1141 km (42.3 ± 43.9 km∙d−1), and energy expenditure of 80460 kcal (2980 ± 1451 kcal∙d−1). Relative to baseline, there were post-challenge decreases in pulmonary capacities and expiratory flows (≤34%), maximum expiratory mouth-pressure (19%), and maximum voluntary ventilation (29%). Heart rate variability deteriorated, manifesting as a 48% decrease in the root mean square of successive differences and a 70% increase in the low-frequency/high-frequency ratio. Pre- to post-challenge endotoxin concentrations were elevated by 60%, with a maximum increase of 130% after a given stage, congruent with an increased frequency and severity of GI symptoms. Conclusions. The challenge resulted in pulmonary and autonomic dysfunction, endotoxaemia and GI distress. The findings extend our understanding of the limits of physiological function and may inform medical best-practice for personnel supporting ultra-endurance events.